Borylation Directed Borylation of Indoles Using Pyrazabole Electrophiles: A One‐Pot Route to C7‐Borylated‐Indolines. Issue 32 (28th June 2022) - Pahl, Jürgen; Noone, Emily; Uzelac, Marina; Yuan, Kang; Ingleson, Michael J.
Abstract: Pyrazabole (1 ) is a readily accessible diboron compound that can be transformed into ditopic electrophiles. In 1 (and derivatives), the B⋅⋅⋅B separation is ca. 3 Å, appropriate for one boron centre bonding to N and one to the C7 of indoles and indolines. This suitable B⋅⋅⋅B separation enables double E−H (E=N/C) functionalisation of indoles and indolines. Specifically, the activation of 1 with HNTf2 generates an electrophile that transforms N−H indoles and indolines into N/C7‐diborylated indolines, with N−H borylation directing subsequent C7−H borylation. Indole reduction to indoline occurs before C−H borylation and our studies indicate this proceeds via hydroboration—C3‐protodeboronation to produce an intermediate that then undergoes C7 borylation. The borylated products can be converted in situ into C7‐BPin‐N‐H‐indolines. Overall, this represents a transient directed C−H borylation to form useful C7‐BPin‐indolines. Abstract : Electrophiles based on pyrazabole are simple to access reagents for the double E−H (E=N/C) borylation of N−H‐indoles/indolines. Due to the robust B2 N4 core of pyrazaboles and a B⋅⋅⋅B separation of ca. 3 Å, the first borylation directs the second to a proximal C−H. For N−H‐indoles, C7‐borylation occurs alongside reduction resulting, post work‐up, in the one‐pot formation of C7‐BPin‐indolines without requiring installation of a directing group.